157k views
1 vote
Solve the equation 5x-2x^2+1

User Harry B
by
4.0k points

1 Answer

4 votes

Answer:

Explanation:

If you call "5x-2x^2+1" an "equation," then you must equate 5x-2x^2+1 to 0:

5x-2x^2+1 = 0

This is a quadratic equation. Rearranging the terms in descending order by powers of x, we get:

-2x^2 + 5x + 1 = 0. Here the coefficients are a = -2, b = 5 and c = 1.

Use the quadratic formula to solve for x:

First find the discriminant, b^2 - 4ac: 25 - 4(-2)(1) = 25 + 8 = 33

Because the discriminant is positive, the roots of this quadratic are real and unequal.

-b ± √(discriminant)

Applying the quadratic formula x = --------------------------------

2a

we get:

-5 ± √33 -5 + √33

x = ----------------- = --------------------- and

2(-2) -4

-5 - √33

---------------

-4

User Eluvatar
by
5.5k points